Injeksi Clenbuterol Menurunkan Lemak Bawah Kulit dan Meningkatkan Bobot Karkas Kambing Pernakan Etawah - Kiranadi, Bambang; Saka, Ketut (Jurnal Veteriner; Vol 10 No 2 (2009))
Twenty growing cross breed etawah goat were treated with clenbuterol every two days. Three levels ofclenbuterol , 5, 10 and 20 ?g/kg BW were injected intramuscularly from the thigh side. The experimentwould like to see the effect of clenbuterol on the metabolism and carcase quality. It was found thatclenbuterol did not affect the gross energy, digestibility, metaboliseable energy and urinary nitrogenexcretion.Clenbuterol will increase the feed intake up to 51.49%. Althoush not affecting protein intake, itsignificantly increased the retain protein from 70.51 up to 149.37%. Subcutaneous carcase weights werereduced between 29.6 up to 51%. Data from carcase quality showed that clenbuterol increase half emptybody weight indicating that clenbuterol is affecting protein metabolism. Dose -respond curve of clenbuterolagainst half empty body weight follows the Michaelis Menten equation and solved by Lineweaver-Burks.Result indicated that the half weight maximum was 5120 gram and Km of clemnbuterol was 9.50 x 10-8M. Clenbuterol is affecting the bone weight carcase but not affecting the intermusculer carcase.
Keywords: Clenbuterol, metabolism, carcase quality